A Comparative Study on Thermal and Non-thermal Processing of Kelulut Honey - Mohd Jan, Muhd Ikmal; Mohd Fauzi, Noor Akhmazillah (Journal of Advanced Industrial Technology and Application, 2021)
Recent years have seen the various studies conducted on the kelulut honey based on their physicochemical and nutritional properties. The main concern in production of kelulut honey in maintaining the quality especially when it is being treated. Previous studies have shown that conventional thermal processing that comprises two phases of heating which are liquefaction and pasteurization will minimize the quality of kelulut honey in terms of its physicochemical and nutritional properties due to its heat sensitivity material criteria. In addition, the reduction in quality of honey due to the unsteady components, breakdown of vitamins and damage of enzymes when it heated at more than 60â„ƒ in thermal processing. Hence, a systematic review is carried out to identify a suitable heat treatment for kelulut honey as compared to conventional thermal processing in treating honey. The search strategy was established in three databases (Google Scholar, PubMed and ScienceDirect) with the search keywords â€œ(â€œHoneyâ€, â€œKelulutâ€, â€œstingless beeâ€, â€œTrigonaâ€, â€œMeliponâ€, â€œMicrowave heatingâ€, â€œDouble boilingâ€, â€œHPPâ€ or â€œHigh pressure processingâ€ and â€œUltrasoundâ€)â€. The data selection strategy was showed using PRISMA guidelines. A total of 311 journal papers were referred to complete this review, however, only 10 articles were highly considered specifically on the process of kelulut honey, where microwave heating, double boiling and high pressure processing (three articles respectively). Whereas, only two articles on analysis of ultrasound were found. From this literature review, it found that HPP provide higher benefit in improving physicochemical and nutritional properties of kelulut honey although it produces a lower change in colour if compared with other treatment. It can be concluded that HPP is the most potential in increasing the quality of kelulut honey followed by double boiling, ultrasound and microwave heating.